BUJANG DARA DALAM MEMPROMOSIKAN PARIWISATA DI KABUPATEN PELALAWAN - Ivony Adytia Saragih; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
One of the benchmarks for increasing regional tourism is the number of tourist visits. As a result, a variety of tourist attractions must be developed in order to attract people to travel. In order to increase tourist visits, it is necessary to have a real role from the output of the selection of Bujang and Dara in carrying out tourism promotion by coordinating and collaborating with tourism entrepreneurs both inside and outside. The aim of this research are: 1) To determine and analyze the role of Bujang and Dara in promoting tourism in the Pelalawan Regency. 2) To determine and analyze Bujang and Dara obstacles in promoting tourism in the Pelalawan Regency. This research used qualitative method. This research took place at the Department of Tourism, Youth and Sports, Pelalawan Regency, at the Bhakti Praja Office Complex, Pangkalan Kerinci, Pelalawan. Researchers collected primary data from the results of interview with the Head of the Bujang and Dara Association, Pelalawan Regency. Secondary data in this research collected from books, hard printed journal from the relevant agencies as a complement to the research process. Data collection techniques in this study are observation, interviews, and documentation. In line with the main problem and focus of this research, the data analysis used is descriptive qualitative. The result of this research is that Bujang and Dara has several roles in carrying out their duties as a Regional Tourism Ambassador. Social Roles and Ceremonial Roles. Social roles include as a speaker, holding social actions, and others. Meanwhile, the ceremonial roles include bridesmaid and bestman. Keyword : : Bujang and Dara, Promotion, Tourism